Contratos que hacen referencia a los rivales y el bien jurídico protegido por la libre competencia - Ybar Abad, Mario (2023)
The analysis of vertical restraints has been carried out mainly through a weighting, case by case, of its anticompetitive effects and likely efficiencies. This is a natural consequence of the conception of competition law as a means to promote consumer welfare and economic efficiency.However, in recent years, a different view has gained strength in the Chilean Supreme Court, according to which, the main goal of competition law is to safeguard the freedom to compete in the market.Given this new approach, the analysis of a particular type of vertical agreements takes on special relevance: contracts that refer to rivals, since, by their very nature, they limit the freedom of third parties external to the agreement.This document analyses the main contracts that refer to rivals, their potential effects on the markets and how its analysis could be subject to changes as the pendulum swings from a competition law aimed at protecting consumer welfare –as currently widely understood– towards a competition law which main goal is to protect the freedom to compete.